Structural modification of supply chains in the imperatives of circular economy - Ivan Kudrenko; Almas Mukhametov; Emin Shahin Aslanov (Journal of Innovation and Entrepreneurship)
Abstract Global economic and environmental challenges in the development of contemporary society underscore the importance of addressing issues related to the structural modification of supply chains within the context of a circular economy. The goal of the study was to identify structural modifications in supply chains in a circular economy, as well as to assess the effectiveness of adapting them to new management approaches through the introduction of information technologies. To achieve this, the research employs a range of statistical methods, including Six Sigma, Pareto analysis, Theory of Constraints, and regression analysis, to identify and address weaknesses within the supply chain. Mathematical computations are utilized to evaluate the effectiveness and necessity of implemented technologies within the supply chain links. The findings of the study demonstrated that the adaptation of supply chains to the conditions of a circular economy significantly reduces operational errors and improves service quality. Specifically, the implementation of blockchain technologies substantially enhances process transparency, increases trust among supply chain participants, and reduces data management costs. However, the transition to circular models encounters several significant challenges, not only of an economic nature but also of social and legal dimensions. The scientific significance of the research lies in the systematization of data on the main directions of supply chain evolution within the framework of a circular economy and the development of a methodology for evaluating the effectiveness of supply chain adaptation to new economic and technological prospects for the development of economic systems. The proposed approaches will enable companies to manage business processes more efficiently, optimize resource management systems, and enhance their resilience to external environmental challenges. Addressing these tasks is a key factor in the successful adaptation of enterprises to dynamic changes in the global economy. The practical application of the results will allow companies not only to reduce operational costs but also to improve the quality of products and services, thereby enhancing their competitiveness in the global market.